SIS: Student Information System for SMKTMI with RBAC - Abd Wahab, Nurul Nadia; Ts. Dr. Zubaile bin Abdullah, (Applied Information Technology And Computer Science, 2025)
Implementing information systems at educational institutions has several advantages, including increased security, better data accessibility and more effectiveness in sharing and managing important data. However, The Ministry of Education's system, which SMK Tunku Mahmood Iskandar (SMKTMI) currently uses to manage student, parent and teacher data has limited capability. In order to overcome these constraints, a web-based Student Information System (SIS) with Role-Based Access Control for SMKTMI is develop. Agile methodology is used and the system was constructed with PHP, HTML, CSS and MariaDB database. The system have modules for class scheduling, academic assessment, attendance tracking and discipline record. It supports Role Based Access Control for admin, teachers, students and parents with security features such as email verification, limited failed login attempt and password policy.